2015
DOI: 10.1016/j.appet.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an acute bout of aerobic exercise on immediate and subsequent three-day food intake and energy expenditure in active and inactive pre-menopausal women taking oral contraceptives

Abstract: 2019 ± 746 kJ vs. 2710 ± 712 kJ; p <0.001, d = -1.00) at the ad libitum lunch. There were no significant differences in energy intake over the four days in active participants and there was a suppression of energy intake on the first day after the exercise experimental day compared with the same day of the control condition in inactive participants (mean difference = -1974 kJ; 95% CI -1048 to -2900 kJ, p = 0.002, d = -0.89). There was a group effect (p = 0.001, d = 1.63) for free-living energy expenditure, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…Men and women were included in eight studies, of which the median percentage of men was 42.2 % (21.5–63.6 %) in the active group and 50 % (21.6–61.6 %) in the inactive group [25, 26, 2832, 37]. Five studies included only men [19, 27, 3335], and one study included only women [36]. …”
Section: Resultsmentioning
confidence: 99%
“…Men and women were included in eight studies, of which the median percentage of men was 42.2 % (21.5–63.6 %) in the active group and 50 % (21.6–61.6 %) in the inactive group [25, 26, 2832, 37]. Five studies included only men [19, 27, 3335], and one study included only women [36]. …”
Section: Resultsmentioning
confidence: 99%
“…A challenge of these studies is distinguishing the individual impact of self-reported physical activity and objectively measured aerobic fitness on these variables as both are inexorably linked. This is pertinent to other studies discussed in this review as all studies that measured VȮ2 peak alongside self-reported habitual physical activity demonstrate that individuals with greater levels of habitual physical activity have higher aerobic fitness levels [35,85,100,[107][108][109]113,116]. Further studies are also needed to verify findings using objective measures of physical activity.…”
Section: Chronic Exercisementioning
confidence: 96%
“…Charlot and Chapelot reported that 24 hour food and macronutrient intakes were similar between high and low activity groups after a 60 minute cycling bout at 70% VȮ2 peak [107]. Underlining the contradictory results, one research group has reported mixed trends in experiments examining the influence of a moderateintensity cycling bout on self-reported food intake in active and inactive groups three days after exercise [108][109][110]. Indeed, in males, Rocha et al [108] demonstrated active individuals compensated more for the exercise-induced energy deficit on the day of exercise, yet the inactive group exhibited greater energy intake on the third day after exercise [108].…”
Section: Acute Exercisementioning
confidence: 97%
See 2 more Smart Citations